2011
DOI: 10.1016/j.jacc.2011.01.011
|View full text |Cite
|
Sign up to set email alerts
|

The Pathology of Neoatherosclerosis in Human Coronary Implants

Abstract: Objectives Human coronary bare metal stents (BMS) and drug-eluting stents (DES) from autopsy cases with implant durations >30 days were examined for the presence of neointimal atherosclerotic disease. Background Neointimal atherosclerotic change (neoatherosclerosis) following BMS implantation is rarely reported and usually occurs beyond 5 years. The incidence of neoatherosclerosis following DES implantation has not been reported. Methods All available cases from the CVPath stent registry (n=299 autopsies),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
331
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 840 publications
(336 citation statements)
references
References 25 publications
3
331
1
1
Order By: Relevance
“…[13][14][15] Recent studies also suggest that DESs may result in endothelial dysfunction manifested through impaired vascular responsiveness in the downstream vessel as well as contributing to late stent thrombosis through neoatherosclerosis. [16][17][18] However, several studies also suggest that cell-cycle inhibitors may possess antiatherogenic properties. [19][20][21][22][23] Although published data are conflicted, it appears that overall outcomes, including target vessel revascularization rates, are slightly more favorable in patients receiving DES, although this has to be weighed against higher stent costs and the necessity for prolonged, uninterrupted antiplatelet therapy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] Recent studies also suggest that DESs may result in endothelial dysfunction manifested through impaired vascular responsiveness in the downstream vessel as well as contributing to late stent thrombosis through neoatherosclerosis. [16][17][18] However, several studies also suggest that cell-cycle inhibitors may possess antiatherogenic properties. [19][20][21][22][23] Although published data are conflicted, it appears that overall outcomes, including target vessel revascularization rates, are slightly more favorable in patients receiving DES, although this has to be weighed against higher stent costs and the necessity for prolonged, uninterrupted antiplatelet therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Although these results demonstrate protection from lesion formation, toxicity of antiproliferative drugs still remains a concern, particularly in tissues affected by infarction because of the potential for inducing a thrombogenic state through platelet dysfunction as well as neoatherosclerosis. 18,31,39 Despite these uncertainties, our findings should encourage a clinical trial with advanced coronary imaging tools to further investigate the effects that DES have on atherosclerosis in downstream vessels.…”
Section: Discussionmentioning
confidence: 96%
“…Although incomplete endothelialization was reported as the primary substrate of late stent thrombosis in an initial pathological study,3, 4 recent reports revealed that abnormal vascular responses are also responsible for the occurrence of late stent failure 5, 6, 7. Such abnormal responses include hypersensitivity reactions, extensive fibrin deposition along with malapposition, and neoatherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent studies suggest that the different characteristics of neointimal tissue seen by OCT may correlate with clinical events such as late stent thrombosis. 20) Kim, et al 21) compared different OCT morphological characteristics with different in-stent neointimal tissue types analyzed by histology and found that the homogeneous pattern of neointimal formation appeared to correlate with less neointimal formation and more favorable vessel healing characteristics when compared with the other optical patterns; the heterogeneous pattern correlated more with the presence of fibrin deposits than the other patterns; the layered pattern correlated with the higher incidence of peri-strut inflammation, neovascularization, and external elastic lamina rupture, which might lead to a higher degree of neointimal proliferation. In a clinical study, Tanaka, et al 22) concluded that in DM patients, the heterogeneous pattern was observed with high frequency.…”
Section: Discussionmentioning
confidence: 99%